2019
DOI: 10.1139/apnm-2018-0392
|View full text |Cite
|
Sign up to set email alerts
|

Camellia oleifera seed extract attenuated abdominal and hepatic fat accumulation in rats fed a high-fat diet

Abstract: The objective of this study was to evaluate the effects of the hot-water extract of defatted Camellia oleifera seeds (CSE) on body and liver fat accumulation in rats. Forty rats were divided into five groups and each group was fed either an isocaloric control diet (C) or a high-fat liquid diet with 0% (H), 0.12% (H1), 0.24% (H2), or 0.48% CSE (H3) for 8 weeks. Ingestion of the high-fat liquid diet increased abdominal and liver fat accumulation, although no difference was found in body weights compared to rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The extracted solution was then filtered, and the filtrate was lyophilised and ground into powder as our CSE sample with a recovery rate of 30 %. The CSE samples contain 81•3 (SD 0•6) mg/g total polyphenols as gallic acid equivalent, 206•3 (SD 8•7) mg/g total saponins as diosgenin equivalent and 6•3 ± 0•4 % total polysaccharides as we previously reported (12) .…”
Section: Preparation Of the Camellia Oleifera Seed Extractsupporting
confidence: 55%
See 3 more Smart Citations
“…The extracted solution was then filtered, and the filtrate was lyophilised and ground into powder as our CSE sample with a recovery rate of 30 %. The CSE samples contain 81•3 (SD 0•6) mg/g total polyphenols as gallic acid equivalent, 206•3 (SD 8•7) mg/g total saponins as diosgenin equivalent and 6•3 ± 0•4 % total polysaccharides as we previously reported (12) .…”
Section: Preparation Of the Camellia Oleifera Seed Extractsupporting
confidence: 55%
“…In the present study, we supplemented 4•5 and 9 g/l in diet of rats with high-fat diet-induced NAFLD according to the results of our preliminary 8-week study (12) and we found that 4•5 g/l can ameliorate hepatic steatosis and inflammation. This dosage was equal to 300 mg/kg per d for rats and 2•9 g/d for a 60 kg human according to the dose conversion calculation of FDA based on body surface area.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Rats were fed lab diet 5001 for a 1‐week adaption and randomly separated into four groups ( n = 7). The normal (N) and CCl 4 control (C) groups were fed a control diet based on AIN‐93M, and the experimental groups were fed with AIN‐93M diets containing 500 or 1000 mg CSE per kg bodyweight (CCL and CCH) according to the effective dosage reported previously (Yang, Yeh, Ko, & Chen, ) for the 8‐week experimental period. In addition, the C, CCL, and CCH groups were subjected hepatic injury by receiving 30% CCl 4 /olive oil (1 mL/kg bodyweight, i.p .)…”
Section: Methodsmentioning
confidence: 99%